Empirical Use of Cephalosporins in Pediatric Infections in Indonesia: A Systematic Review - Melisa Rezki Puspitasari; Tifany Maulida Candra; Agung Endro Nugroho; Ika Puspita Sari (Majalah Farmaseutik, 2026)
Cephalosporins, particularly third-generation agents like ceftriaxone, remain widely used in pediatric populations in Indonesia despite declining effectiveness due to high rates of ESBL-producing pathogens. This systematic review synthesized evidence on cephalosporin use, resistance patterns, and effectiveness in Indonesian children across various clinical settings, based on five studies published between 2019–2025. Data included study characteristics, patient profiles, indications, and outcomes. Ceftriaxone was the most common empirical choice for infections such as sepsis, pneumonia, and urinary tract infections. However, susceptibility of Escherichia coli and Klebsiella pneumoniae was often below 30%, whereas amikacin and meropenem maintained over 90% activity. Notably, one tertiary pediatric ward reduced ESBL prevalence after restricting ceftriaxone use, demonstrating the potential of targeted stewardship programs. The findings reveal a disconnect between prescribing practices and resistance data, emphasizing the need for real-time microbiological surveillance, updated pediatric empirical therapy guidelines, and improved prescriber education. Strengthening pediatric antimicrobial stewardship is crucial to preserving antibiotic effectiveness and optimizing clinical outcomes in children amid rising resistance.